Differences in Insula and Pre-/Frontal Responses during Reappraisal of Food in Lean and Obese Humans - Kumar, Saurabh; Grundeis, Felicitas; Brand, Cristin; Hwang, Han-Jeong; Mehnert, Jan; Pleger, Burkhard (Frontiers in Human Neuroscience, 2016)
Brain regions involved in the reappraisal of tasty but unhealthy foods are of special interest for the development of new therapeutic interventions for obesity, such as non-invasive brain stimulation or neurofeedback. Here, we visually presented food items (i.e., high/low caloric) to obese and lean individuals during EEG recordings, while they either admitted or regulated their food desire. During admitting the desire for low and high calorie foods, obese as well as lean individuals showed higher activity in the left dorsolateral prefrontal cortex (DLPFC), whereas the right frontal operculum was involved in the reappraisal of the same foods, suggesting interplay between executive control and gustatory regions. Only in lean participants, we found an interaction between calorie content and the regulate/admit conditions in bilateral anterior insular cortices, suggesting that the anterior insula, assumed to primarily host gustatory processes, also underpins higher cognitive processes involved in food choices, such as evaluating the foods’ calorie content for its reappraisal.